Disaster and Destination: Sustainable Tourism Governance in North Bandung Area - Wulung, Shandra Rama Panji (Universitas Bina Sarana Informatika, 2025)
Tourism contributes to sustainable development, but in its development, it is very vulnerable to disasters. In this study, disasters are categorized into natural and non-natural disasters. Collaboration between stakeholders is needed to reduce disaster risk as a form of sustainable tourism destination governance. This study aims to analyze sustainable tourism destination governance and their relation to disasters. This qualitative research was conducted in March-August 2022 in the North Bandung Area. Primary data was obtained through interviews and observations, while secondary data was obtained through policy documents, literature, and previous research. The data obtained were then carried out with content analysis, descriptive statistical analysis, and qualitative descriptive analysis. The results showed that the West Bandung Regency Tourism and Culture Office as a destination management organization in the North Bandung Area tended to have implemented sustainable tourism programs during the pandemic, especially in the promotion and crisis management subcategories.